The Application Of The Just-in-time Philosophy In The Chinese Construction Industry - Low , Sui Pheng; Gao , Shang (Penerbit Universiti Sains Malaysia, 2011)
The Just-in-Time (JIT) philosophy originated from the Toyota Production System (TPS) and has been used in the manufacturing industry for many decades. It has helped to increase the productivity of the industry and has also increased the quality of its products. In recent years, numerous studies in developed countries have endeavoured to introduce JIT in the construction industry to reap similar benefits. This study focused on applying JIT to the Chinese construction industry with the goal of improving its performance and thus its competitiveness. This paper discusses the current state of the Chinese construction industry; presents the potential impediments to implementing JIT; and proposes a framework for JIT implementation in the areas of design, procurement, construction and inspection. The results of this study suggest that government and educational institutions should play a key role in spearheading the application of JIT in the construction industry in China.